2020
DOI: 10.1177/1753466620980267
|View full text |Cite
|
Sign up to set email alerts
|

Is thoracoscopy superior to thoracotomy in the treatment of congenital lung malformations? An updated meta-analysis

Abstract: Background: A meta-analysis was performed for a comparison of outcomes between video-assisted thoracoscopic surgery (VATS) and thoracotomy for congenital lung malformations (CLM). Methods: Electronic databases, including PubMed, Scopus, Embase, and the Cochrane Library were searched systematically for literature aimed mainly at reporting the therapeutic effects for CLM administrated by VATS and thoracotomy. Results: A total of 40 studies meeting the inclusion criteria were included, involving 2896 subjects. VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
9
1
Order By: Relevance
“…This meta‐analysis showed no significant deviation between thoracoscopic lobectomy and thoracotomy in terms of chest tube length of stay, transfusions, and postoperative length of stay. These results are not consistent with the meta‐analysis published by Junhua Xie et al ., 25 but suggest that thoracoscopic lobectomy does not increase the postoperative associated risks compared to thoracotomy. An interesting difference was observed between the two groups, with a lower overall complications rate for thoracoscopic lobectomy than for thoracotomy, contrary to most previous studies.…”
Section: Discussioncontrasting
confidence: 87%
“…This meta‐analysis showed no significant deviation between thoracoscopic lobectomy and thoracotomy in terms of chest tube length of stay, transfusions, and postoperative length of stay. These results are not consistent with the meta‐analysis published by Junhua Xie et al ., 25 but suggest that thoracoscopic lobectomy does not increase the postoperative associated risks compared to thoracotomy. An interesting difference was observed between the two groups, with a lower overall complications rate for thoracoscopic lobectomy than for thoracotomy, contrary to most previous studies.…”
Section: Discussioncontrasting
confidence: 87%
“…Concurrently, thoracoscopic procedures have become an increasingly popular operative approach for CLMs patients due to improved cosmesis [ 18 ]. A recent meta-analysis found fewer post-operative complications, shorter length of hospital stay, but increased operative time in thoracoscopic procedures [ 19 ]. However, conflicting clinical results can present in CLMs resections with different operative approaches because of retrospective review limits.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one study 34 found that the incidence of complications increased with the age of the patient at the time of surgery, and most of the complications were related to pleural problems, mainly including air leakage and fluid accumulation 35 . Air leakage at the surgical site can lead to surgical emphysema and pneumothorax, while fluid accumulation can lead to chylothorax, and in severe cases they may lead to accidental re-intubation or even reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Minor complications include superficial surgical site infection, superficial wound rupture, and urinary tract infection. In particular, musculoskeletal complications including breast deformity, rib fusion,chest wall asymmetry,pterygoid scapulae and scoliosis are the major long-term complications of thoracotomy 36 , which have a bad effect on children in skeletal development during growth 35 . A cohort study published by Markel M et al demonstrated that compared with the general population, children experience more frequent respiratory infections after resection of congenital lung malformations, and Resection does not eliminate the increased risk of pneumonia 37 .…”
Section: Discussionmentioning
confidence: 99%